KNOWLEDGE AND PERCEPTION REGARDING ARTIFICIAL INTELLIGENCE IN NURSING AMONG STAFF NURSES - Kavikuilrani B; Rajarajeshwari V; Ezhilarasi S; Sharmila G; Sharmila S; Sharmila S; Sheby D (The Bioscan, 2025)
Background: Artificial Intelligence (AI), is the ability of computers to perform tasks typically associated with human intelligence, can impact millions of patients by changing how medicine is practiced. Integrating AI into nursing practice could significantly streamline workflows, reduce errors, and improve care efficiency by automating routine tasks and providing real-time decision support. Aim and Objective: To assess the knowledge and perception regarding AI in nursing among staff nurses. Methodology: A quantitative approach and descriptive design was chosen for this study among 204 staff nurses in Panimalar Medical College Hospital and Research Institute (PMCH&RI). A Convenient sampling technique was used to select samples who fulfilled the inclusion criteria. The structured knowledge questionnaire, 3 point likert scale were used to assess the level of knowledge and perception. Results: The study findings revealed that 64.21% and 51.96% of samples had inadequate knowledge and low perception level. The calculated r-value r=0.29 for knowledge and perception showed a very high statistical significant at p=0.001, it’s indicate a positive correlation between knowledge and perception. Conclusion: The study results depicted that the staff nurses' knowledge of AI in nursing increases, their perceptions toward it are likely to improve. The study suggests that to ensure the effective adoption of AI in nursing, it is crucial to invest in education, training, and institutional support, empowering nurses to embrace these technologies and improve patient care. Keywords Artificial Intelligence, knowledge, perception.